Le BnF DataLab, un service aux chercheurs en humanités numériques - Marie Carlin; Arnaud Laborderie (Humanités Numériques)
Over the past ten years, the huge increase of digital collections at the National Library of France (BNF) — Gallica, Internet archives, metadata, etc. — has opened up new perspectives, raising the issue of how researchers use heritage data. To meet these uses and needs, the BNF is setting up a new service: the BnF DataLab, aimed to support research teams in constituting and processing digital corpora. This place is designed for individual and collaborative work and opened in October 2021.